Anaemia and its associated factors among pregnant women in Malaysia - Minhat, Halimatus Sakdiah; Thangarajah, Puganeswary (Nutrition Society of Malaysia, 2022)
Introduction: Despite remarkable improvement in maternal health, anaemia during pregnancy remains a significant public health threat to Malaysian women. This study aimed to determine the prevalence, severity, and associated factors of anaemia in pregnancy among pregnant mothers in Seremban, Negeri Sembilan. Methods: A total of 482 pregnant mothers were recruited using cluster sampling. Data were collected using a validated and pre-tested self-administered questionnaire consisting of four sections, namely socio-demographic and socioeconomic details, obstetric history, nutritional factors, and iron supplementation status. In this study, anaemia in pregnancy was defined as haemoglobin (Hb) <11.0 g/dL, which was based on blood test taken during the first trimester. The data were analysed using IBM SPSS version 23.0. Multiple logistic regression analysis was conducted to determine the predictive model for anaemia during pregnancy among the respondents. Results: The prevalence of anaemia in pregnancy among the respondents was 22.0%, with 95.3% respondents mildly anaemic. Respondents with an intake of iron supplementation of once daily (AOR=0.191, 95% CI: 0.074- 0.914), more than once daily (AOR=0.149, 95%CI: 0.091-0.248), and low intake of seafood (AOR=0.320, 95% CI: 0.187-0.526) were less likely to develop anaemia during pregnancy. Conclusion: The findings revealed moderate level of anaemia in pregnancy, which was dominated by those in the mild category, with increased risk predicted among young mothers. Iron supplementation (once daily or more) and low intake of seafood protected mothers from developing anaemia during pregnancy.